Physiological characteristics of Japanese elite synchronized swimmers - Takamoto, M.; Nakamura, Y.; Motoyoshi, M.; Mutoh, Y.; Miyashita, M. (Swimming Science V, 1988)
Synchronized swimming requires a high degree of artistic movement. Its performance was formerly so graceful and sophisticated that most of the routine events were comprised of floating and movement of the arms to music. However, it has become dynamic and powerful and is now a competitive Olympic event. Sychronized swimming has aroused scientists' interest, and several studies report data on Canadian and American synchronized swimmers. Synchronized swimmers in Japan have also been playing an important part in the world; however, knowledge and data on Japanese synchronized swimmers are limited. Thus, the purpose of this study was to investigate the physical and physiological characteristics of Japanese elite synchronized swimmers.